Association between serum 25-hydroxyvitamin D levels and pulmonary function, among Korean adults, during 2010–2014, by sex, age, and body mass index. (July 2018) - Shim, Sun-Young; Chae, Won-Jeong; Kim, Hyeon-Chang; Park, Eun-Cheol; Jang, Sung-In
Abstract: Background: This study examined the association between serum 25-hydroxyvitamin D (25(OH)D) and pulmonary function, among Korean adults, from 2010 to 2014. Methods: The data were obtained from the fifth Korea National Health and Nutrition Examination Survey (KNHANES 5), and the first and second year (2013–2014) of KNHANES 6. The study population comprised 14, 378 individuals. The variable of interest was serum 25(OH)D, and the dependent variable, pulmonary function. Results: All people with vitamin D levels below 30 ng/ml had lower lung functions, which was significant in lower forced expiratory volume in the first second (FEV1) (serum 25(OH)D < 10 ng/ml, 20 to <30 ng/ml: P = .001, 10 to <20 ng/ml: P = 0) and forced vital capacity (FVC) (serum 25(OH)D level <10 ng/ml: P = .01, 10 to < 20 ng/ml: P = .001, 20 to <30 ng/ml: P = .008). The lower the serum 25(OH)D, the lower the levels of FEV1 in men and this was significant. (serum 25(OH)D < 10 ng/ml: P = .007, 10 to <20 ng/ml: P = .002, 20 to <30 ng/ml: P = .007). The values of FEV1 and FVC were lower in people aged 50–69 years when vitamin D was lower than 30 ng/ml which were all significant. Among participants with BMI values < 23 kg/m 2, lower vitamin D levels were significantly associated with lower pulmonary function. Conclusions: We found a significant association between serum 25(OH)D and pulmonary function, and this was related to sex, age and body mass index.